TANTANGAN GURU DAN STRATEGI DIFERENSIASI DALAM MENGAJAR MATEMATIKA PADA KELAS HETEROGEN - Subadi, Diva Nurfiana; Niswah, Hulwatun; Ningrum, Septiyani Daya; Dewanti, Sintha Sih (Universitas Insan Budi Utomo, 2026)
Technological advancements and the dynamics of educational paradigms in the 21st century require teachers to accommodate the diverse learning needs of students through flexible, student-centered approaches. In mathematics learning, the diversity of abilities, learning styles, and readiness of students in heterogeneous classrooms becomes a challenge that requires adaptive teaching strategies, one of which is differentiated instruction. This study aims to describe the challenges faced by teachers in teaching mathematics in heterogeneous classrooms and to analyze the differentiation strategies applied by teachers to address the differences in students' learning needs. The study uses a descriptive qualitative approach with the subject being a high school mathematics teacher in the Special Region of Yogyakarta. The data collection method was conducted through semi-structured interviews and documentation, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the success of differentiated mathematics learning in heterogeneous classes depends not only on the methods used but also on the teacher's sensitivity in understanding the students' characteristics, readiness, background, and perceptions of mathematics learning.